2020
DOI: 10.1001/jamapediatrics.2020.3651
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Nasopharyngeal Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Levels in Patients With Mild to Moderate Coronavirus Disease 2019 (COVID-19)

Abstract: had full access to all the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
284
7
9

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(332 citation statements)
references
References 8 publications
27
284
7
9
Order By: Relevance
“…Furthermore, the shedding of SARS-CoV-2 in the upper respiratory tract of pediatric patients lasted 11.43 days, which is comparable with adults (13). A Chicago study showed that children with COVID-19 younger than 5 years old had 10-100 times viral load compared with children more than 5 years old and adults with COVID-19 (14). A series of 228 diagnosed SARS-CoV-2 infections in France indicated that the incidence of COVID-19 infection increased by 7.4-fold in children between 1 and 5 years old (15).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, the shedding of SARS-CoV-2 in the upper respiratory tract of pediatric patients lasted 11.43 days, which is comparable with adults (13). A Chicago study showed that children with COVID-19 younger than 5 years old had 10-100 times viral load compared with children more than 5 years old and adults with COVID-19 (14). A series of 228 diagnosed SARS-CoV-2 infections in France indicated that the incidence of COVID-19 infection increased by 7.4-fold in children between 1 and 5 years old (15).…”
Section: Discussionmentioning
confidence: 86%
“…The first pediatric case of COVID-19 was identified on March 10th, 2020; by May 31st, 158 cases of children under 18 years had been reported, with a median [IQR] age of 12 [4][5][6][7][8][9][10][11][12][13][14][15][16] years (table 1). Temporal distribution showed two different time-peaks, the first in the second half of March likely secondary to infections acquired before lock-down measures, and the second through the second half of April 2020 till the end of May likely due to the increased number of RT-PCR performed between March (n=987) and May (n=8,073) (figure 1 and figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Also, in the Netherlands periodic reports from the National Institute of Public Health showed that patients under 20 years play a smaller role in the spread of the infection than adults [5]. However, studies exclusively based on SARS-CoV-2 viral load in respiratory samples suggest a possible role of children in SARS-CoV-2 transmission, even when asymptomatic [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional single-centre study in 145 consecutive patients, with mild to moderate symptomatic COVID-19, Heald-Sargent et al found that children younger than 5 years of age had higher SARS-CoV-2 RNA levels in their nasopharyngeal swabs than children aged 5 to 17 years and adults. 12 A limitation of the study was that asymptomatic children infected with SARS-CoV-2 were not included.…”
Section: Viral Rna Levelsmentioning
confidence: 99%
“…9,10 This caused some to prematurely conclude that children are considerably less important drivers of SARS-CoV-2 transmission than adults. 11 However, recent reports have suggested high viral loads in nasopharyngeal swabs of symptomatic young children, 12 and a high degree of transmission among children and adolescents attending an overnight youth camp. 13…”
mentioning
confidence: 99%